Development of software tools for modeling and analysis of systems using extended Petri nets - Musa, Kazi Abul Faruk Md; Nanda, Navnit Kumar; Vilas Wuwongse; Phan, Minh Dung; Japan - ADB. (Bangkok : Asian Institute of Technology, 1990)
A software for Basic Petri net was developed in an earlier thesis (SHRESTHA, 1989) which is used for Specification, Modeling, Simulation and Analysis of Basic Petri nets. The present work is an extension of this, which focuses mainly on Timed Petri Net with a Timed Place approach . A Specification Language is developed for proper net representation which is passed through a Parser for Syntactic and Semantic checking of the specification and develops necessary data structure for graphical representation of the timed net. An interactive Graphical Editor is used for drawing the net which is later used in the Simulation Module for providing the user with progress of simulation visually . A Rea.1-Time ~imulation module is developed by which the dynamic behavior ·of the modeled system can be viewed and its interactive nature provides the user to make adjustment to the timing and initial marking for a desired net property . Reachability analysis technique has also been implemented for the generation of possible transition sequences for the Reachability tree and as well as for different net properties. Subnet modeling facilitates for analyzing part of a large system and thus serves as a convenient tool for hierarchical net modeling . These subnets can be individually simulated. In addition to these features for Timed Petri net, a module for Matrix analysis of Basic Petri net has also been implemented which verifies the conservativeness property and the checks for deadlock detection in the net structure. The features of Timed Petri net have been integrated with the Basic Petri net software to present a comprehensive packa~1e which is a versatile tool for performance evaluation of wide range of systems.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1990
Keywords: Petri nets